2003
DOI: 10.1002/ajmg.a.20196
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of genetic counselors with molecular genetic testing laboratories: Implications for non‐geneticist health care providers

Abstract: The availability of molecular genetic tests for the identification of mutant gene carriers, and for assessing individual genetic response to pharmacologic agents, infectious agents, and other environmental exposures, is expected to result in the increased use of the molecular genetic testing laboratory by primary care physicians. However, a number of concerns have been raised about such testing including the need for safeguards to protect patient privacy, and if the interface between genetic testing laboratori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…8 These findings, consistent with other published observations, suggested that in many cases test result reports are neither standardized nor contain complete interpretations. 1,[3][4][5]7 Our findings and those reported in the literature raise concerns that benefits from genetic tests may be compromised, in some instances, as a consequence of improper test ordering, variations in the reporting of results, and the capacity of clinicians and their staff to effectively use the information contained within test result reports.…”
mentioning
confidence: 66%
“…8 These findings, consistent with other published observations, suggested that in many cases test result reports are neither standardized nor contain complete interpretations. 1,[3][4][5]7 Our findings and those reported in the literature raise concerns that benefits from genetic tests may be compromised, in some instances, as a consequence of improper test ordering, variations in the reporting of results, and the capacity of clinicians and their staff to effectively use the information contained within test result reports.…”
mentioning
confidence: 66%
“…In one publication, clinical GCs said that they had contacted a member of the molecular laboratory staff in advance of sending a sample 58% of the time. 4 When contacting the laboratory, over 94% of the time the clinician asked for information regarding cost, TAT, and specimen requirements. 4 Although these are important things to know when ordering DNA testing, the purpose of this article is to describe a number of other ways that the laboratory staff can be helpful to health care professionals who wish to order a genetic test.…”
Section: Discussionmentioning
confidence: 99%
“…4 When contacting the laboratory, over 94% of the time the clinician asked for information regarding cost, TAT, and specimen requirements. 4 Although these are important things to know when ordering DNA testing, the purpose of this article is to describe a number of other ways that the laboratory staff can be helpful to health care professionals who wish to order a genetic test. We feel strongly that the job description of the laboratory GC includes not only serving as a resource to the referring clinician, but also advocating for them and their patients within the lab.…”
Section: Discussionmentioning
confidence: 99%
“…Practicing physicians do not think they have enough information about genetic diseases or genetic counseling and recognize their need for more education. McGovern et al 22 found that 79% of genetic counselors participated in the general education of physicians about genetic testing. The need for this education and its benefits in primary care have been defined by Kolb et al 23 and Kirk.…”
Section: Sources Of Knowledgementioning
confidence: 99%